The diagnostic assessment of 21st century skills acceptable for introduction in the educational process within the framework of teaching English - Abdilmanova, D.R.; Olkova, I.A. (KSU Publ., 2020)
In conditions of a rapidly growing economy and the information society, it has become necessary to prepare specialists with broader professional competencies that are 21st century skills. This article discusses the main peculiarities of 21st century skills diagnostic assessment revealed as a result of the analysis of various authors’ scientific works. Taking into consideration the distinguished peculiarities of the diagnostic assessment of these skills, the author of the article has developed a diagnostic test and assessment criteria to determine a level of the formation of the most important 21st century skills that are acceptable for implementation in the educational process within the framework of teaching English at higher education institution. As a result of the experimental testing of the developed diagnostic test and assessment criteria with the participation of the students of M. Kozybaev NKSU, the main disadvantages of training future qualified English teachers have been uncovered. The results of this study are acceptable for use in further scientific works when developing 21st century skills teaching methods and assessment criteria and integrating them into the higher education system of Kazakhstan that will contribute to providing the country with highly qualified workforce in the foreseeable future.
Ағылшын тілін оқыту шеңберінде оқу процесіне енгізуге қолайлы XXI ғасырдың дағдыларын диагностикалық бағалау
Диагностическое оценивание навыков XXI века, приемлемых для внедрения в учебный процесс в рамках обучения английскому языку
Keywords: 21st century skills; diagnostic assessment; assessment criteria; a level of the formation of 21st century skills; foreign language teaching; English; higher-order thinking; higher education in Kazakhstan